Biomimetic electroconductive nanofibrous matrices for skeletal muscle regenerative engineering. - Tang, Xiaoyan (Regen Eng Transl Med, 2019)
The regeneration of the muscles of the rotator cuff represents a grand challenge in musculoskeletal regenerative engineering. Several types of matrices have been proposed for skeletal muscle regeneration. However, biomimetic matrices to promote muscle regeneration and mimic native muscle tissue have not been successfully engineered. Besides topographical cues, an electrical stimulus may serve as a critical cue to improve interactions between materials and cells in scenarios fostering muscle regeneration. In this in vitro study, we engineered a novel stimuli-responsive conductive nanocomposite matrix, and studied its ability to regulate muscle cell adhesion, proliferation, and differentiation. Electroconductive nanocomposite matrices demonstrated tunable conductivity and biocompatibility. Under the optimum concentration of conductive material, the matrices facilitated muscle cell adhesion, proliferation, and differentiation. Importantly, conductive aligned fibrous matrices were effective in promoting myoblast differentiation by upregulation of myogenic markers. The results demonstrated promising potential of aligned conductive fibrous matrices for skeletal muscle regenerative engineering.